Global progress on adaptation implementation - Leiter, Timo; Njuguna, Lucy; Singh, Chandni (2025)
The Adaptation Gap Report 2025: Running on Empty updates the cost of adaptation finance needed in developing countries, putting it at US$310 billion per year in 2035, when based on modelled costs. When based on extrapolated needs expressed in Nationally Determined Contributions and National Adaptation Plans, this figure rises to US$365 billion a year. Meanwhile, international public adaptation finance flows to developing countries were US$26 billion in 2023: down from US$28 billion the previous year. This makes adaptation financing needs in developing countries 12-14 times as much as current flows. If current finance trends continue, the Glasgow Climate Pact goal of doubling international public adaptation finance from 2019 levels by 2025 will not be achieved, while the New Collective Quantified Goal for climate finance is not ambitious enough to close the finance gap. The private sector could do more – with potential to provide around US$50 billion per year if backed by targeted policy action and blended finance solutions. While far from enough, there is visible progress on closing the planning and implementation gap. Most countries have at least one national adaptation policy, strategy or plan in place; countries are getting better at mainstreaming adaptation into wider national development planning; and countries reported on over 1,600 implemented adaptation actions, mostly on biodiversity, agriculture, water and infrastructure. Climate fund support for new adaptation projects rose in 2024, although emerging financial constraints make the future unclear. Both public and private finance must step up to increase adaptation, taking care not to increase the proportion of debt instruments used by vulnerable nations.